2007
DOI: 10.21000/jasmr07010771
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Commercial Hardwoods on Reclaimed Minesoils in West Virginia: 6th Year Results

Abstract: Recent changes to West Virginia coal mining regulations emphasize commercial forestry as a preferred post-mining land use on surface mined areas. In the spring of 2001, a study was initiated in northern West Virginia to examine the establishment and growth of commercial hardwood trees on a reclaimed surface mined site. We planted seeds and 1-0 seedlings of five hardwood species [red oak (Quercus rubra L.), black cherry (Prunus serotina Ehrh.), black walnut (Juglans nigra L.), white ash (Fraxinus americana L.),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Black locust and white ash exhibited 100% survival across all treatments and have repeatedly performed well in mine spoil environments (Emerson et al,, 2009;Skousen et al,, 2007;Angel et al" 2006;Ashby et al" 1985), Chestnut oak was the only species to show significant differences in survival by treatment, with the highest survival occurring in the brown sandstone (92%) followed by the gray sandstone (78%), mixed (54%), and shale (39%) treatments.…”
Section: Results and Discussion Tree Growth And Productivitymentioning
confidence: 91%
“…Black locust and white ash exhibited 100% survival across all treatments and have repeatedly performed well in mine spoil environments (Emerson et al,, 2009;Skousen et al,, 2007;Angel et al" 2006;Ashby et al" 1985), Chestnut oak was the only species to show significant differences in survival by treatment, with the highest survival occurring in the brown sandstone (92%) followed by the gray sandstone (78%), mixed (54%), and shale (39%) treatments.…”
Section: Results and Discussion Tree Growth And Productivitymentioning
confidence: 91%
“…Ashes are early‐succession species well adapted to a mine site environment. Zeleznik and Skousen (1996) as well as Skousen et al (2007) identified white ash as the best surviving species in their minesoil studies. Harlow and Harrar (1968) also say that ashes are known to be very tolerant at the seedling stage as they are abundant in a forest's understory.…”
Section: Resultsmentioning
confidence: 99%
“…Some annual or perennial grasses can grow much taller than the young seedlings in the early stages of development and smother the seedlings when the aerial portions die back in the winter. In addition, a heavy groundcover also provides cover for small mammals which feed on the bark and girdle trees (Skousen et al, 2007; Torbert et al, 2000). Torbert and Burger (2000) showed less‐competitive herbaceous species to be a better option when seeding ground cover for reforestation sites.…”
mentioning
confidence: 99%